The Duke Employee Weight Loss Program: Report of a Duke Diet and Fitness Center Pilot Study - Leonor Corsino; A. Garrett Hazelton; Howard Eisenson; Crystal Tyson; Laura P. Svetkey; Ronald Sha; Truls Ostbye; Ruth Q. Wolever (Occupational Health and Safety Society of Nepal, 2016)
Background: Obesity is increasingly prevalent in the industrialized world. Obese workers have two times the number of workers' compensation claims as those of non-obese workers. Worksite interventions may be especially effective because employees spend a large part of their day in the work environment, and both employee and employer have incentives to improve the employees' health. Objective: To assess the impact of a 4 week employee intervention in participant's weight, body fat and blood pressure. Methods: This was a pilot study. We assessed feasibility and impact compared to baseline at 4 weeks, 6 months, and 12 months post-program. The primary outcomes were weight and body mass index. Secondary outcomes included percent body fat and blood pressure. Results: Forty participants consented to be part of the study. Baseline weight was 97.8 kg [SD ± 17.05]. Twelve months post-intervention weight loss averaged 2.7 kg [SD ± 6.35]. One-way repeated measures ANOVA showed a significant effect of participation on weight, body mass index, and percent body fat. Conclusion: Significant improvements in the primary outcomes were observed in participants completing our worksite pilot study, indicating that a worksite weight loss intervention is potentially effective